Analisis Faktor yang Berhubungan dengan Kelelahan Kerja pada Pegawai Di UPT Puskesmas Kota Karang Kota Bandar Lampung Tahun 2024 - Kristianto Putro, Wisnu; Modjo, Robiana (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to assess the risk factors that affect fatigue in employees of UPT Puskesmas Kota Karang, Bandar Lampung City. This research design is quantitative with a cross-sectional approach, involving the entire employee population of 71 people as a sample through total sampling technique. The analysis was done with chi-square test and odds ratio using SPSS. The results showed that domestic dependents and other occupations had a significant association with health worker fatigue. In contrast, variables such as age, tenure, sleep quantity, and sleep quality showed no significant association. The conclusion of this study is that external factors outside of work contribute to the level of fatigue of health workers. Therefore, managerial interventions that take into account the workload as well as domestic dependents and additional work of employees are essential to improve the quality of service and the welfare of health workers in health centers.